2017
DOI: 10.5539/elt.v10n12p182
|View full text |Cite
|
Sign up to set email alerts
|

Engaging ESP Students with Brain-Based Learning for Improved Listening Skills, Vocabulary Retention and Motivation

Abstract: The concept of teaching and learning has changed drastically over the past few years by the virtue of both research results carried out in the fields of second/Foreign language learning and acquisition. Of all these researches, findings related to the brain structure and functions in cooperation with cognitive aspects of the education process, including the study of learning styles and intelligence have struck the language learning domain. A due understanding of learners' learning styles, emotional preferences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
2
11
0
4
Order By: Relevance
“…According to the previously mentioned literature and related studies, some conclusions can be stated as follows:  Some of the studies that mentioned BBL as the independent variable did not illustrate the features of the brain-based treatment or how the BBL principles and stages of BCT were implemented and some other studies limited it to using (3-5) strategies (e.g. Lago, & Seepho, 2012;Akyurek, & Afacan, 2013;Nafa, 2013;Abd El-Maksoud, 2016;Salem, 2017;Parnell, 2018). This might indicate deficient understanding and implementation of BBL as it is a comprehensive approach that requires not only diversifying the learning and teaching strategies but also requires considering motivational aspects, managing the learning environment, and refining assessment techniques and tools.…”
Section: Teacher Professional Developmentmentioning
confidence: 99%
“…According to the previously mentioned literature and related studies, some conclusions can be stated as follows:  Some of the studies that mentioned BBL as the independent variable did not illustrate the features of the brain-based treatment or how the BBL principles and stages of BCT were implemented and some other studies limited it to using (3-5) strategies (e.g. Lago, & Seepho, 2012;Akyurek, & Afacan, 2013;Nafa, 2013;Abd El-Maksoud, 2016;Salem, 2017;Parnell, 2018). This might indicate deficient understanding and implementation of BBL as it is a comprehensive approach that requires not only diversifying the learning and teaching strategies but also requires considering motivational aspects, managing the learning environment, and refining assessment techniques and tools.…”
Section: Teacher Professional Developmentmentioning
confidence: 99%
“…Of course, mediated learning and novel communication technologies along with the productive use of the Internet should be encouraged in ESP classrooms. Since listening comprehension material and interesting authentic listening material help vocabulary retention (Salem, 2017), teachers" understanding of learners" learning styles may be supported by using infinitely many sources such as podcasts mentioned earlier (www.thenakedscientists. com, www.chemistryworld.com, www.nature.com, https://player.fm/podcasts, etc.)…”
Section: Situation-based Learning and First-hand Experiencementioning
confidence: 99%
“…Oghyanous (2017) found that the effect of brain-based teaching approach toward self-efficacy of EFL students in Iran was significant. Brain-based learning was also proven to be effective in developing listening skills of the students and consolidating the recalling and the retention of the students' vocabulary as well as maximizing the motivation of the students in learning the skills of language (Salem, 2017). This was followed by Khalil et al (2019) whose research result showed that some speaking skills of EFL students were developed because of the effect of the implementation of brain-based learning in the speaking class.…”
Section: Introductionmentioning
confidence: 99%